Macroeconomic Modelling of Natural Resource Effects: A Review of the Literature - علي عيسى (Dirasat in Economics and Business, 2019)
This paper reviews the literature analysing a dynamic macroeconomic effects arising from natural resource (oil) related shocks. The dynamic models considered in this paper were divided into two categories; short-run and long run models. The short-run theoretical models emphasise that natural resource sector affects the economy through a number of channels including: resource movement; spending; income; and exchange rate effects, emphasising the demand side in a dynamic modelling context. However, a number of deficiencies of shortrun models were considered in the long-run models, and this in turn resulted in a divergence in the adjustment process derived from the short-run models from those derived from the long-run models. The long-run models emphasise that, in addition to short-run effects, natural resource sector affects the economy during long run through capital stock accumulation (an additional wealth effect), foreign asset stock accumulation via the current account (a current account effect), human capital stock accumulation (a Labour productivity effect) and imported capital stock accumulation via capital imports (a technology effect). Specifically, they emphasise the supply side in a dynamic modelling context. The paper concluded that the knowledge of the consequences of the adjustment process during the long term is important to the government and economic agents to identify alternative policies that can be implemented in order to overcome some of the undesirable features of the adjustment process, and thereby minimize the adverse effects and/or boost the benefits from resource (oil) related shocks. JEL classification: E27, E60, Q33, Q43, Q48.